Prognostic and immunological role of sulfatide-related lncRNAs in hepatocellular carcinoma - Huang, Xing Feng; Fu, Li Sheng; Cai, Qian Qian; Fan, Fei (Frontiers in Oncology, 2023)
Abstract Background: Hepatocellular carcinoma (HCC) is the most common primary malignancy of the liver. Long non-coding RNAs (lncRNAs) play important roles in the occurrence and development of HCC through multiple pathways. Our previous study reported the specific molecular mechanism of sulfatide's regulation of integrin αV expression and cell adhesion in HCC cells through lncRNA AY927503. Therefore, it is urgent to reveal more sulfatide-related lncRNAs, explore these lncRNAs’ clinical signifcance, and find new targeted treatment strategies. Methods: Microarrays were used to screen for a complete set of lncRNAs with different expression profiles in sulfatide treated cells. Sulfatide-related lncRNAs expression data and corresponding HCC patient survival information were obtained from the TCGA database, and the prognosis prediction model was constructed based on Cox regression analysis. MeRIP-seq was used to identify the effect of sulfatide on lncRNAs m6A modification. TIMER and GSEA were used to enrich the immune and functional pathways of Sulfatide-related lncRNAs. Results: We screened 85 differentially expressed lncRNAs (DE-lncRNAs) (|FC|>2, P<0.05) in sulfatide-treated HCC cells, 24 sulfatide-related lncRNAs were highly expressed in HCC tissues, 6 of which were associated with poor prognosis in HCC patients. Based on this,we constructed a sulfatide-related lncRNAs prognosis assessment model for HCC. According to this risk score, the overall survival (OS)curve showed that the OS of high-risk patients was significantly lower than that of low-risk patients (P<0.05). It was worth noting that the expression difference of sulfatide-related lncRNA NRSN2-AS1 may be related to sulfatide-induced RNA m6A methylation, and the expression level of NRSN2-AS1 was significantly positively correlated with immune cell infiltration in HCC, and participated in peroxisome and PPAR signaling pathways. Conclusions: In conclusion, sulfatide-related lncRNAs might be promising prognostic and therapeutic targets for HCC.